2020
DOI: 10.1001/jamadermatol.2019.4212
|View full text |Cite
|
Sign up to set email alerts
|

Core Outcome Set for Actinic Keratosis Clinical Trials

Abstract: IMPORTANCE Although various treatments have been found in clinical trials to be effective in treating actinic keratosis (AK), researchers often report different outcomes. Heterogeneous outcome reporting precludes the comparison of results across studies and impedes the synthesis of treatment effectiveness in systematic reviews.OBJECTIVE To establish an international core outcome set for all clinical studies on AK treatment using systematic literature review and a Delphi consensus process.EVIDENCE REVIEW Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
1
37
0
3
Order By: Relevance
“…Outcome measures that were assessed in the studies included scarring, healing time, histological assessment, patient satisfaction and re‐epithelialization time. These outcome measures were similar to the recently established core outcome set for treatment of actinic keratoses and are included in Table 2 11 . The majority of studies reported on clearance, recurrence or progression rates, on adverse events (AEs), long‐term follow‐ups, cosmetic outcomes, patient satisfaction and some reported on treatment discontinuation, dosage adherence or healing time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcome measures that were assessed in the studies included scarring, healing time, histological assessment, patient satisfaction and re‐epithelialization time. These outcome measures were similar to the recently established core outcome set for treatment of actinic keratoses and are included in Table 2 11 . The majority of studies reported on clearance, recurrence or progression rates, on adverse events (AEs), long‐term follow‐ups, cosmetic outcomes, patient satisfaction and some reported on treatment discontinuation, dosage adherence or healing time.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we assessed the adverse effects of these treatment modalities. We also evaluated the reporting of the recently defined core outcome set of actinic keratoses (complete clearance, treatment percentage of actinic keratoses cleared, severity of adverse events, patient perspective on effectiveness, patient‐reported future treatment preferences and recurrence rates) 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, these factors are important to improve the acceptability of and compliance to treatment regimens [11,12]. Surprisingly, the patient-centered motives and expectations towards AK treatment have received little attention until now but can represent a major barrier for treatment adherence [13][14][15]. Here, we report the results of a German-wide, multicenter, cross-sectional study to gain insight into the management of AK by investigating patient attitudes, expectations, and motives.…”
Section: Introductionmentioning
confidence: 99%
“…An international core outcome set for all clinical trials on AK treatment has been recently published by the Core Outcome Measures in Effectiveness Trials (COMET) Initiative and the Cochrane Skin Group Core Outcomes Set Initiative (CSG-COUSIN). Core outcome set parameters included percentage of AKs cleared, complete clearance of AKs, severity of adverse events, patient perspective on effectiveness, patient-reported future treatment preference, and rate of occurrence [ 18 ]. The international experts and patients recognized the importance of including the efficacy endpoint ‘percentage of AKs cleared’ in their core outcome set.…”
Section: Discussionmentioning
confidence: 99%